Metascientific reflections on the Science Teaching. Possible Contributions from the Communicative Perspective of Jürgen Habermas (Papeles, 2021)
In this article we will deal firstly the relevance of the Science Teaching, at its different levels, from a metascientific point of view.  Then, we will develop the conception of communicative rationality, in its various aspects, of the contemporary German thinker Jürgen Habermas. This will allow us to think of the Teaching of Science as a fundamental area for promoting critical thinking.
Keywords: science teaching; communicative rationality; criticism